Maternal Psychological Problems Associated with Neonatal Intensive Care Admission. (27th July 2009) - Yurdakul, Ziya; Akman, Ipek; Kuşçu, M. Kemal; Karabekiroglu, Aytul; Yaylalı, Gulsum; Demir, Figen; Özek, Eren
Abstract : Background . Mothers of infants admitted to a neonatal intensive care unit (NICU) are believed to have heightened distress. The purpose of this paper was to determine depression and anxiety symptoms and attachment style in NICU mothers. Methods . The NICU group consisted of mothers whose infants were admitted to the NICU and the control group consisted of mothers of healthy term infants. The psychosocial assessments were done at the first month. Results . The mean Edinburgh Postpartum Depression (EPDS) score of NICU mothers was significantly higher than that of the control group mothers (9.6 ± 5.6 versus7.3 ± 4.9, P = .005 ). NICU mothers who had high EPDS (≥ 13) scores had significantly higher anxiety scores and insecure attachment style in comparison to the subgroup of NICU mothers who had low EPDS scores. Conclusion . Mothers of NICU babies had higher EPDS scores. Mothers who had higher EPDS scores had higher anxiety scores as well. These NICU mothers should receive appropriate counseling during the hospitalization of their babies.